Leveraging Technology Untuk Meningkatan Kualitas Kinerja Tenaga Kesehatan: Tinjauan Literature Teori - Alma Marinda; Vip Paramarta; Diki Tri Bagus Dermawan; Riyan Putri Kumorowani; Cepi Hidayatuloh (Pusat Riset dan Inovasi Nasional, 2023)
In various countries the use of information technology in fields that present aspects of goodness in everyday life. This is to improve the quality of the performance of health workers to streamline their time, skills and abilities. In addition, technology can also be accessed via computers or other modern tools that support health services. Leverage technology as the ability to create increased value with a stable or shrinking amount of resources, while at the same time enhancing the ability to grow more rapidly. The purpose of this theoretical literature review is to find out how leveraging technology can improve the quality of the performance of health workers. The research method used by the author, namely theoretical review, is a theoretical approach used by researchers to explain research problems. This method is to review or review various literature that has been published by academics or other researchers. The results of this theoretical literature review are leveraging technology to improve the quality of performance of health workers, namely by increasing understanding, using technology effectiveness and increasing targets. It can be concluded that the more a person can develop and improve their abilities in the field of technology, the more technologies are created which will have an impact on the quality of performance that a person gets. So, nothing is impossible to present and use the advanced information technology of the future. For health workers the use of technology as a system based on smart technology. It is hoped that health workers will always hone their skills, learn new things, and have the ability to apply modern technology. This can make the performance assessment of health workers to improve the reputation of the institution.